Pandion haliaetus Osprey WA - Vilas Boas da Frota, Angélica; Vitorino, Breno Dias; da Silva, Carolina Joana; Ikeda-Castrillon, Solange Kimie; Nunes, Josué Ribeiro da Silva (Zenodo, 2020)
Pandion haliaetus (Linnaeus, 1758) Material examined. Tables 1, 2. IDentificAtion. This species was observed foraging on the Paraguay River during all hydrological periods, although it is classified as migratory. We identified this eagle by the combination of its white head and bottom and the presence of a black band behind the eye, which extends onto the upper part of the body (Sick 1997). : Published as part of Vilas Boas da Frota, Angélica, Vitorino, Breno Dias, da Silva, Carolina Joana, Ikeda-Castrillon, Solange Kimie & Nunes, Josué Ribeiro da Silva, 2020, Birds of the Ramsar site Estação Ecológica de Taiamã and buffer zone, Pantanal wetlands, Brazil, pp. 401-422 in Check List 16 (2) on page 414, DOI: 10.15560/16.2.401 : {"references": ["Sick H (1997) Ornitologia brasileira. Nova Fronteira, Rio de Janeiro, 912 pp."]}